Are Chinese Workers Paid the Correct Wages? Measuring Wage Underpayment in the Chinese Industrial Sector, 2005-2010. (September 2015) - Xu, Zhun; Chen, Ying; Li, Minqi
This paper examines the labor compensations of the Chinese industrial sector for the period 2005-2010. We find that both the state owned enterprises and the non-domestic enterprises pay more than the living wage. But the domestic private enterprises pay substantially less than the living wage. We also find that all types of Chinese industrial enterprises pay the workers with wages that are substantially less than their marginal product of labor.